Linear algebra and learning from data - Strang, Gilbert (Wellesley-Cambridge Press, 2019)
This book provides a comprehensive introduction to linear algebra, emphasizing conceptual understanding and practical applications. It covers fundamental topics such as vectors, matrices, determinants, eigenvalues, eigenvectors, and linear transformations. Real-world applications in engineering, computer science, and data analysis are included to illustrate the relevance of linear algebra.